Enhanced oral bioavailability of two Cistanche polysaccharides in acteoside: an in-depth analysis of intestinal flora, short-chain fatty acids, and pharmacokinetic regulation - Lian, Jing; Zhang, Yuan; Dong, Kexu; Shi, Ji; Zhang, Fan; Shan, Guoshun; Liu, Pengpeng; Wang, Nan; Jia, Tianzhu (Frontiers in Nutrition, 2025)
IntroductionFor centuries, Cistanche deserticola Y. C. Ma has been considered to have the effect of “tonifying the kidney and strengthening the yang,” and is used for the prevention and treatment of diseases such as impotence, female infertility, lumbago and senile constipation. Polysaccharides and small molecules of acteoside are the main chemical compounds co-existing in Cistanche deserticola Y. C. Ma with health benefits, but the interaction of these two compounds in vivo is not yet known.MethodsHere, we investigated the effects of unprocessed Cistanche polysaccharides and wine-processed Cistanche polysaccharides on the metabolism of acteoside in vivo through gut microbiota. Male Sprague–Dawley rats were randomly divided into Control group, unprocessed Cistanche polysaccharide group (UCP group) and wine-processed Cistanche polysaccharide group (WCP group). After 21 days of intervention with unprocessed Cistanche polysaccharides and wine-processed Cistanche polysaccharides, rats were given 100 mg/kg of acteoside on day 22. Acteoside and its associated metabolites pharmacokinetically studied were analysed using UPLC-QqQ-MS, and the composition of short-chain fatty acids (SCFAs) in excrement was measured using the technique of GC–MS. The microbiological composition of the intestines was discovered using 16S rRNA gene amplicon sequencing.ResultsThe results showed that the Cistanche polysaccharides used in this experiment, including unprocessed Cistanche polysaccharides and wine-processed Cistanche polysaccharides, could regulate the diversity of gut microbiota and increase the number of beneficial bacteria, especially wine-processed Cistanche polysaccharides were able to promote the growth of Ligilactobacillus and Duncaniella genus, and improve the production of SCFAs and the absorption of acteoside.DiscussionBy exploring the synergistic effects of large molecules Cistanche polysaccharides and small molecule acteoside, this paper provides a new explanation for the scientific use of plant-derived polysaccharides to improve the bioavailability of oral drugs.